Economic Evaluation and Challenges of Waste Management and Recycling: A Case Study in Nisombalia District, Maros Regency - Sibali, Alwi (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
This study examines the challenges and solutions in waste management and recycling in Nisombalia District, Maros Regency. The main focus of the study is to identify the factors that affect public awareness and participation in recycling programs, as well as evaluate the effectiveness of the policies implemented. The study found that the lack of socialization and education, the lack of public perception, and the limited infrastructure are the main factors that affect low participation in recycling. The phenomenon of the gap between ideal policies and practices in the field is also a significant issue, showing that policy implementation needs to be adjusted to local needs and involve community participation. The results of the study show that to improve the effectiveness of waste management and recycling, a comprehensive and participatory approach is needed. Improving public education, building accessible recycling facilities, and adapting policies to local cultures are key steps. By overcoming these challenges and reducing the gap between policy and practice, it is hoped that the recycling program can achieve optimal results and provide significant benefits to the community and the environment in Nisombalia District.Keywords: Waste Management, Recycling, Community Participation